Structural Model of Motor Readiness of Young Gymnasts Aged 6-8 - О. Худолій; Т. Карпунець; О. Іващенко (OVS LLC, 2015)
The purpose of the research is to determine the factor structure of the motor readiness of young gymnasts aged 6-8. Research methods. To achieve the tasks set, the research relies on theoretical and empirical methods used: analysis and collation of scientific and methodological literature; modeling, pedagogical observations and experiment, factor analysis. The research recorded the following indicators: the number of repetitions required to teach the exercises; score for the unit-directional movement coordination exercise (test 3); score for the differently directed movement coordination exercise (test 4); error in spatial precision of hand movements (test 9); error in spatial accuracy of leg movements (test 14); error in time accuracy of executing the sitting-to-lying event (test 17); error in time accuracy of five jumps on marks in 5 seconds (test 18); error in evaluation of muscular efforts with visual control (test 24); error in evaluation of muscular efforts without visual control (test 25); vestibular stability, error (test 28); wrist strength; back strength; standing long jump. The participants in the study were 40 gymnasts aged 6-7 and 32 gymnasts aged 7-8. Research results. The young gymnasts aged 6-8 have quite distinct elements that determine the development of their sports skills, namely: learning ability, motor experience, coordination complexity of exercises; relationship between the strength development and the ability to differentiate muscular efforts; movement coordination, movement control and vestibular apparatus stability.